Exploring the mechanism of Glycyrrhiza glabra and Curcuma domestica against skin photoaging based on network pharmacology - Oktavia Rahayu Adianingsih; Fifi Farida Fajrin; Christopher Kuncoro Johan (Indonesian Journal of Biotechnology, 2024)
Excessive exposure to UV radiation results in skin photoaging, which may be prevented or treated using natural plant compounds. Herbal cosmetics and medicines have grown in popularity due to the abundance of relatively safe compounds. This research aims to explore the network pharmacology of Glycyrrhiza glabra (GG) and Curcuma domestica (CD) against skin photoaging. Active compounds from GG‐CD were sourced from databases including TCSMP, KnapSack, TCMID, and published literature, while disease targets were collected from GeneCards and OMIM databases. The STRING database was utilized to construct the protein‐protein interaction (PPI) network. Enrichment analyses for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway were performed using Metascape. The herb‐compounds‐target‐pathway‐disease (H‐C‐T‐P‐D) network was visualized using Cytoscape software. A total of 529 compounds, 2,335 active compound targets, and 120 skin aging targets were obtained. GO enrichment revealed 1,635 biological processes, 67 cellular components, and 121 molecular functions. The study suggests that GG and CD have the potential to treat skin photoaging by targeting multiple targets, such as TP53, TNF, AKT1, IL6, and IL‐1B, as well as multiple pathways, such as those in cancer, apoptosis, TNF, IL‐17, and the AGE‐RAGE signaling pathway. Experiment validation is necessary to confirm the preliminary network pharmacology results.